Future smart grids creation and dimensionality reduction with signal handling on smart grid using targeted projection - Musa Jaber, Mustafa; Ali, Mohammed Hasan; CB, Sivaparthipan; Asaad, Renas Rajab; Agrawal, Ruchi (Sustainable Computing: Informatics and Systems, 2024)
A smart grid is a developing electrical network of transmission lines, switches, transformers, protection equipment, sensors, and information technologies working together and are the result of a dynamic co-evolution process that leverages the integration of technological advances. These are facing several challenges with renewable energy resources, has high consumption, and the ever-increasing demand for electricity at commercial, residential, and industrial levels. In recent decades, the main grid is facing several challenges related to the integration of renewable energy resources, deployment of grid-level energy storage devices, deployment of new usages such as the electric vehicle, massive usage of power electronic devices at different electric grid stages, and the inter-connection with microgrids and prosumers. This paper aims to identify the challenges, control these perspectives, for attaining the energy infrastructures, to achieve the directions of future research and development, with respect to power generation, transmission, distribution, and consumption. In this study, future smart grids creation and dimensionality reduction with signal handling on the smart grid using, targeted projection pursuit for future smart grids signal analysis is proposed, in which the Signal handling on the smart grid uses Blind equalization and is imposed to transmit the signal which is inferred from the received signal. The smart grid is based on the Non-negative matrix factorization; the Sallen-key topology is implemented to reduce the noise in the signal. Moreover, in this paper, we perform the targeted projection pursuit, the Cognitive Dimensionality Reduction is used for the analysis of n-way arrays, nonlinear dimensionality reduction, and we use the Linear predictive coding, and Hilbert spectrum which represents the spectral envelope of a digital signal of speech in the compressed form. The experiments on the proposed method, show the effectiveness of our method is 92 % well organised with extensive results at Targeted projection pursuit for future smart grids. The signal analysis shows the execution between past research and the ongoing research has achieved an efficiency rate of 92.2 %, in which the current approach outperforms 94.87 % compared existing approach. The analysis of future smart grids creation, Signal Dimensionality Reduction is 75 % higher than the existing analysis. The proposed system flow is performed with more versatility, and energy efficiency is 75.65 % and 34.54 % efficiency than the existing system.
Keywords: smart grids creation; signal handling